2012
DOI: 10.1371/journal.pgen.1003127
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of Heterochromatin Is Limited to Specific Families of Maize Retrotransposons

Abstract: Transposable elements (TEs) have the potential to act as controlling elements to influence the expression of genes and are often subject to heterochromatic silencing. The current paradigm suggests that heterochromatic silencing can spread beyond the borders of TEs and influence the chromatin state of neighboring low-copy sequences. This would allow TEs to condition obligatory or facilitated epialleles and act as controlling elements. The maize genome contains numerous families of class I TEs (retrotransposons)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
142
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 63 publications
7
142
2
Order By: Relevance
“…The nearest elements were classified as terminal inverted repeat (TIR) elements, LTR_spreading, or LTR_nonspreading. The spreading or nonspreading is based upon the assignments from a previous study in which some families of LTR elements were found to result in spread of DNA methylation to low-copy flanking sequences (Eichten et al 2012). The error bars and significance ("*") of the random sets of probes were determined in the same method used in A.…”
Section: Discussionmentioning
confidence: 99%
“…The nearest elements were classified as terminal inverted repeat (TIR) elements, LTR_spreading, or LTR_nonspreading. The spreading or nonspreading is based upon the assignments from a previous study in which some families of LTR elements were found to result in spread of DNA methylation to low-copy flanking sequences (Eichten et al 2012). The error bars and significance ("*") of the random sets of probes were determined in the same method used in A.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, all of the six most abundant LTR-retro families that we investigated exhibit high overall levels of internal DNA methylation and H3K9me2 in B73 aerial tissues, as well as spreading of these heterochromatic modifications into adjacent regions of ;1 to 2 kb (Eichten et al, 2012). Nonetheless, members of many of the highly abundant LTR-retro families are closely interspersed with genes in the euchromatic arms of maize chromosomes (SanMiguel et al, 1996;Liu et al, 2007;Baucom et al, 2009).…”
Section: Diversity Of Replication Timing In Te Familiesmentioning
confidence: 93%
“…TEs, which typically contain high levels of DNA methylation and the repressive histone modification H3K9me2 in maize (Eichten et al, 2012;Regulski et al, 2013;West et al, 2014), are traditionally thought of as silenced chromatin. Specifically, all of the six most abundant LTR-retro families that we investigated exhibit high overall levels of internal DNA methylation and H3K9me2 in B73 aerial tissues, as well as spreading of these heterochromatic modifications into adjacent regions of ;1 to 2 kb (Eichten et al, 2012).…”
Section: Diversity Of Replication Timing In Te Familiesmentioning
confidence: 99%
“…It is unclear how pure epigenetic variation could occur, but failure to faithfully maintain methylation patterns by methyltransferase has been proposed as one possible mechanism (Schmitz et al 2011). Alternatively, DNA methylation variation could be dependent on genetic polymorphisms such as structural rearrangements (Melquist et al 1999) or polymorphic transposon insertions (Martin et al 2009;Eichten et al 2012;Yang et al 2013) that occur near the affected region. DNA methylation variation could also be triggered by signals from trans-acting loci (Cao and Jacobsen 2002;Riddle and Richards 2002;Bender 2004).…”
mentioning
confidence: 99%